Internal Audit Enhances Internal Control Over Cash Receipts Within F&B Distribution - Enur Halimah; Roro Endah Kumalasari (P3M, Sekolah Tinggi Ilmu Ekonomi Pasundan Bandung, 2026)
This study investigates the significant influence of internal audit on the internal control of cash receipts, highlighting its crucial role in enhancing company development. Effective internal control over cash not only boosts the company's growth but also minimizes the chances of errors and fraud. The primary objective is to understand how internal audits function, the current state of internal cash receipt controls, and the impact of internal audits on these controls. Utilizing a descriptive quantitative approach, the research collects data through questionnaires distributed to thirty individuals. The statistical methods employed include correlation analysis, simple linear regression, and coefficient of determination analysis, following validity and reliability testing of the data. Findings indicate that both internal audit and sales internal control possess fairly good average values. The simple linear regression shows that internal audit does indeed affect internal control. It reveals that internal audit significantly contributes to the effectiveness of cash receipt control, while a portion remains influenced by factors like underutilized human resources and incomplete procedures. The novelty of this research lies in its specific focus on the food and beverage distribution sector, revealing how targeted internal audits can systematically enhance cash receipt controls unique to this industry. The implications suggest that strengthening internal audit practices could lead to substantial improvements in cash management and overall organizational efficiency.